Tahfiz schools entry requirement and characteristics of tahfiz students - Che Hassan, Norlizah; Mohd Fakhruddin, Fathiyah; Mohd Ayub, Ahmad Fauzi; Abd Mutalib, Lukman; Wan Jaafar, Wan Marzuki (OCERINT International Organization Center of Academic Research, 2015)
Tahfiz education is among the growing education that has gained attraction among Malaysians nowadays. The establishment of Tahfiz schools by government and private sector is a clear sign that the Tahfiz education will start to fill mainstream education in Malaysia. In line with this, the study is conducted to explore the characteristics of Tahfiz students and to understand what are the main criteria of admission for Tahfiz schools. This study is a qualitative research and eight students from three Tahfiz schools were involved as research participants. The findings showed several important criteria for the admission to tahfiz schools. The entry requirement would require the applicants to go through several important interviews. Among the criteria evaluated by the interviewers are the ability to read Quran and the understanding of the tajwid, memorizing abilities, academic excellence, student interests and attitudes. The findings provided important implications that are important for Tahfiz schools to have a clear standard in selecting their students. This will help the school and parents, especially in training and preparing their children for Tahfiz school entry in order to produce more Huffaz (those who memorize the entire Qur’an).